Enhancing Motivation and Science Learning Outcomes of Elementary School Students using Animated Video: A Quasi-Experimental Study - Inwanti, Safitri Nur; Setiawan, Deni (Jurnal Pendidikan MIPA, 2025)
IPAS learning, especially the material “My Indonesia is Rich in Culture” in elementary schools, still uses conventional media. The use of this media causes low student motivation, which has an impact on their interest, enthusiasm, and enthusiasm in participating in learning. Unattractive media often makes students bored quickly, so the delivery of material is not optimal. As a result, student learning outcomes are also unsatisfactory. One of the media that can increase students' interest and enthusiasm is animated video. This study aims to analyze and describe the effectiveness of learning media on motivation and learning outcomes in IPAS subjects. This type of research is a quantitative experiment with a quasi experimental design. The design used was nonequivalent control group design, with the population consisting of class IVA (27 students) as the experimental class and class IVB (27 students) as the control class, a total of 54 students. Data were collected through tests to measure learning outcomes and questionnaire sheets to measure learning motivation. Data analysis used Independent Sample t Test to test the difference and effectiveness of animated video media. The results showed that the application of animated video media was more effective than conventional media in learning IPAS material “My Indonesia is Rich in Culture.” The average value of student motivation in the experimental class reached 77.85, while in the control class it was only 74.15. For learning outcomes, the experimental class average was 85.96, compared to the control class which was 69.74. From the results of this study, it can be concluded that animated video media is more effective than conventional methods. Therefore, teachers are advised to innovate with more interesting learning media.       Keywords: animated video, motivation, learning outcomes.